Seismic performance of shape memory alloy reinforced concrete moment frames under sequential seismic hazard. (August 2020) - Abraik, Emad
Abstract: Damage may accumulate in structures that are exposed to multiple earthquakes, mitigating their ability to withstand after future ground shaking. Several recent studies have focused on improving the post-earthquake functionality of structures by using re-centering devices or materials. Superelastic shape memory alloy (SE-SMA) material has received considerable attention from the seismic community. However, the extensive cost of SE-SMA as reinforcement restricts its commercial use. This paper aims first to introduce a new hybrid plastic hinge (HPH), which combines the steel and SE-SMA bars within the critical sections to reduce construction costs and enhance the seismic performance of reinforced concrete (RC) frame buildings. The HPH RC buildings are comprehensively evaluated under sequence ground motions. Results showed superior seismic performance of the HPH RC buildings when compared to the conventional SE-SMA system, which was fully reinforced by the SE-SMA bars in critical sections. As part of this ongoing investigation, an approximate method proposed by FEMA P-58 (2018) to estimate residual drift demands were discussed.